The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/ldr.3171
|View full text |Cite
|
Sign up to set email alerts
|

Post‐little ice age paraglacial processes and landforms in the high Iberian mountains: A review

Abstract: Three Iberian mountain ranges encompassed glaciers during the Little Ice Age (LIA):the Pyrenees, Cantabrian Mountains, and Sierra Nevada. The gradual warming trend initiated during the second half of the 19th century promoted the progressive shrinking of these glaciers, which completely melted during the first half of the 20th century in the Cantabrian mountains and Sierra Nevada and reduced by 80% of their LIA extent in the Pyrenees. In these formerly glaciated environments, the transition between glacial and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 70 publications
(128 reference statements)
0
33
0
1
Order By: Relevance
“…The degradation of relict ice and permafrost has been also detected in other Iberian high mountain environments glaciated during the LIA, such as in the Pyrenees and the Cantabrian Mountains . Similarly, evidence of degradation of perennial ice deep in the ground has also been reported in several karstic environments across the Mediterranean region: recent studies have reported shrinkage of the ice volume stored in ice caves as well as a decrease in the extent of permanently frozen ground existing in these sporadic permafrost environments in the Cantabrian Mountains, Pyrenees, Italy, Croatia and Greece, among others.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…The degradation of relict ice and permafrost has been also detected in other Iberian high mountain environments glaciated during the LIA, such as in the Pyrenees and the Cantabrian Mountains . Similarly, evidence of degradation of perennial ice deep in the ground has also been reported in several karstic environments across the Mediterranean region: recent studies have reported shrinkage of the ice volume stored in ice caves as well as a decrease in the extent of permanently frozen ground existing in these sporadic permafrost environments in the Cantabrian Mountains, Pyrenees, Italy, Croatia and Greece, among others.…”
Section: Discussionmentioning
confidence: 65%
“…Lanjarón, Rio Seco and Dílar valleys) . As occurred during the post‐LIA phase in the rock glacier that exists in the Veleta cirque, the formation of permafrost‐related features – including rock glaciers and protalus lobes – must have been conditioned by highly active paraglacial processes, with very unstable rock walls that produced large quantities of sediment, which must have trapped ice that no longer featured glacial dynamics . This process has also been detected in other environments of the Iberian mountains, such as the Central and Eastern Pyrenees .…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations